Determining Factors for Startup Success in Indonesia: Perspective of Young Entrepreneurs - Nicholas Lachlan; Olivia Smith (Pandawan Sejahtera Indonesia, 2024)
The entrepreneurial ecosystem in Indonesia is expanding rapidly, driven by the active involvement of young entrepreneurs. However, the factors influencing the success of these startups remain understudied. This research aims to explore the key determinants of startup success from the perspective of young entrepreneurs in Indonesia. A mixed-methods approach was adopted, incorporating both quantitative surveys and qualitative interviews with startup founders. The quantitative data was analyzed using SmartPLS, while thematic analysis was applied to the qualitative insights. The findings reveal that market adaptability, financial management, mentorship, and innovation are the primary factors contributing to the success of startups. These elements are crucial in shaping the sustainability and growth of startups in the Indonesian context. Understanding these factors can provide valuable insights for aspiring entrepreneurs, investors, and policymakers, helping to create a supportive environment for startup development and success.